Recent Credit Surge in Historical Context - Ohnsorge, Franziska; Yu, Shu (World Bank, Washington, DC, 2016)
Benign financing conditions since the global financial crisis and, more recently, rising financing needs have fueled a rapid increase in credit to the nonfinancial private sector, especially to the corporate sector, in emerging markets and developing economies. Credit growth has been most pronounced, and nearing the pace associated with past credit booms, in commodity exporting countries. In contrast, in commodity importers, credit-to-gross domestic product ratios are elevated but have been stable or shrinking over the past few years. That said, in a few, mostly energy exporting, emerging and developing countries, credit to the private sector is now near levels that have been associated with past episodes of financial stress.